2018
DOI: 10.1007/s11695-018-3376-8
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic-Guided Transversus Abdominis Plane (TAP) Block as Part of Multimodal Analgesia in Laparoscopic Roux-en-Y Gastric Bypass Within an Enhanced Recovery After Surgery (ERAS) Program: a Prospective Randomized Clinical Trial

Abstract: ClinicalTrials.gov Identifier: NCT03203070.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…Numerous studies indicate that TAP blocks can effectively provide analgesia following laparoscopic abdominal surgery, thus increasing their popularity in ERAS protocols. 7 – 10 , 27 31 However, anesthesia and pain medicine literature continue to question the utility of TAP blocks in these cases. 3 , 11 This discrepancy in evidence, or interpretation of evidence, makes it difficult to identify best clinical practices.…”
Section: Transversus Abdominis Plane Blocksmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies indicate that TAP blocks can effectively provide analgesia following laparoscopic abdominal surgery, thus increasing their popularity in ERAS protocols. 7 – 10 , 27 31 However, anesthesia and pain medicine literature continue to question the utility of TAP blocks in these cases. 3 , 11 This discrepancy in evidence, or interpretation of evidence, makes it difficult to identify best clinical practices.…”
Section: Transversus Abdominis Plane Blocksmentioning
confidence: 99%
“… 51 Studies have demonstrated improvements in the components of ERAS protocols with TAP blocks. 7 – 10 However, a large meta-analysis and comprehensive systematic review challenge these proposed benefits. 3 , 11 …”
Section: Clinical Impactmentioning
confidence: 99%
See 1 more Smart Citation
“…BioMed Research International including general surgeries [10][11][12][13][14][15][16], gynecological and obstetric surgeries [17][18][19][20][21][22], urinary surgeries [23], and nephrology surgeries [24].…”
Section: Flowchart Of the Literature Search And Studymentioning
confidence: 99%
“…2 More recently, Ruiz-tovar and colleagues replicated our results using a 6-point technique in patients undergoing Roux-en-Y gastric bypass within an enhanced recovery after surgery program. 3 Saber et al 1 used an US-guided two-point technique at the midclavicular line. Although the study was well-designed and adequately powered, no significant differences were noted in the outcome measures except for postoperative pain score at 3 hours after surgery.…”
Section: Dear Editormentioning
confidence: 99%